Avascular necrosis of the jaw resulting from sickle cell disease - Roland-Billecart Thomas; Maes Jean-Michel; Vieillard Marie-Helene; Ferri Joël; Nicot Romain (EDP Sciences, 2021)
Sickle cell disease (SCD) is a hemoglobin disorder characterized by the presence of abnormal haemoglobin. The deformed cells cause the blood to be more viscid, leading to vaso occlusive crises (VOC). We report an osteonecrosis of the jaw resulting of a VOC in a patient with sickle cell disease. Dental infections, particularly apical cysts, appear to be local factors favouring mandibular infarcts associated with sickle cell disease.